2004
DOI: 10.1128/jb.186.14.4705-4713.2004
|View full text |Cite
|
Sign up to set email alerts
|

Altering Toluene 4-Monooxygenase by Active-Site Engineering for the Synthesis of 3-Methoxycatechol, Methoxyhydroquinone, and Methylhydroquinone

Abstract: Wild-type toluene 4-monooxygenase (T4MO) of Pseudomonas mendocina KR1 oxidizes toluene to p-cresol (96%) and oxidizes benzene sequentially to phenol, to catechol, and to 1,2,3-trihydroxybenzene. In this study T4MO was found to oxidize o-cresol to 3-methylcatechol (91%) and methylhydroquinone (9%), to oxidize m-cresol and p-cresol to 4-methylcatechol (100%), and to oxidize o-methoxyphenol to 4-methoxyresorcinol (87%), 3-methoxycatechol (11%), and methoxyhydroquinone (2%). Apparent V max values of 6.6 ؎ 0.9 to 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
70
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 79 publications
(73 citation statements)
references
References 45 publications
(66 reference statements)
3
70
0
Order By: Relevance
“…The different regioselectivities shown by BMMs have been attributed previously to differences in the shape of the active site pocket, an idea supported by the fact that several point mutations in the active sites of T4MO, toluene p-monooxygenase, ToMO, MMO, and B. cepacia G4 T2MO cause large variations in the regioselectivities of these BMMs (2,7,26,30,34,35). In a previous paper (4), we have reported that mutations at position 103 of the A subunit change the regioselectivity of ToMO from Pseudomonas sp.…”
mentioning
confidence: 82%
“…The different regioselectivities shown by BMMs have been attributed previously to differences in the shape of the active site pocket, an idea supported by the fact that several point mutations in the active sites of T4MO, toluene p-monooxygenase, ToMO, MMO, and B. cepacia G4 T2MO cause large variations in the regioselectivities of these BMMs (2,7,26,30,34,35). In a previous paper (4), we have reported that mutations at position 103 of the A subunit change the regioselectivity of ToMO from Pseudomonas sp.…”
mentioning
confidence: 82%
“…The ␤-galactosidase activities were calculated, based on a protein concentration of 0.24 mg protein/ml/OD 600 unit (53). Each experiment was repeated with a second independent culture.…”
Section: Methodsmentioning
confidence: 99%
“…All vials were shaken at 30°C and 600 rpm (Vibramax 100; Heidolph, Nurenberg, Germany), and the reaction was stopped periodically (a vial was removed at each time period) by filtration of the cells. The progress of enzymatic hydroxylation of PEA was measured by reverse-phase high-performance liquid chromatography (HPLC), and the initial transformation rates (calculated as the amount of PEA decreased in the culture supernatant) were determined by sampling at 0.5-to 20-min intervals during the first 2 to 5 h. The specific activity (nmol/min/mg protein) was calculated as the ratio of the initial transformation rate and the total protein content (0.24 mg protein/ml/OD 600 for T4MO [30]). Activity data reported in this paper are based on at least two independent results.…”
Section: Methodsmentioning
confidence: 99%